Extremism within the family - Gil S. Epstein (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2006)
This paper considers an economic analysis of intergenerational transition of ethnic and social trait. We consider the level of social traits chosen by parents and its effect on their children's choice of ethnic and social traits when reaching adulthood. We develop a theory that suggests that parents will chose extreme ethnic and social traits in order to increase the cost that their children will pay if they wish to deviate from their parent's "ideal". The extreme choice of the ethnic social traits of parents has an effect on the segregation of minorities and migrants.
Keywords: F22; J1; D1; 330; intergenerational transition; ethnic trait; social trait; minorities; migrants